Unique muscularity in cyclists' thigh and trunk: A cross-sectional and longitudinal study - Ema, R.; Wakahara, T.; Yanaka, T.; Kanehisa, H.; Kawakami, Y. (Scandinavian Journal of Medicine & Science in Sports, 2016)
This study examined the influence of regular training in competitive cycling on individual muscle volume of the thigh and psoas major cross-sectionally and longitudinally. T1-weighted magnetic resonance (MR) images of the trunk and right thigh were obtained from eight experienced varsity male cyclists (experience: >4 years) and 10 untrained men (experiment 1), and from 12 (10 males, two females) varsity cyclists before and after competitive cycling training for 6 months (experiment 2). From the MR images, the volumes of each of the quadriceps femoris and hamstrings, total adductors, gracilis, sartorius, and psoas major were determined. The volumes of the monoarticular thigh muscles, semitendinosus, and psoas major muscles were significantly greater in the experienced cyclists than in the untrained men (experiment 1), and increased significantly after the competitive training for 6 months (experiment 2). In contrast, the volumes of the other biarticular thigh muscles were similar among the experienced cyclists and untrained men (experiment 1), and did not change by competitive cycling training (experiment 2). The results indicate that competitive cycling training induces muscle-specific hypertrophy of the synergistic muscles, especially between the monoarticular and biarticular muscles, leading to quantitative profiles of the musculature in experienced cyclists.